Performance trials on different rates and ratios of N and P fertilisation in Ethiopia to inform field-specific Maize-Nutrient-Management advisory - Sida, Tesfaye Shiferaw; Andersson, Jens A.; Hijbeek, Renske (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This report of the Scaling Readiness of Nutrient Management decision Support Tools project focuses on agronomic trials that serve to inform the development of scalable, field-specific advisory for maize farmers in Ethiopia. These trials were conducted to generate additional information required to make a mobile phone-based nutrient decision support tool – Maize-Nutrient-Manager – more scalable in the context of institutional limitations in fertilizer availability and distribution in Ethiopia. The focus of the trials is on establishing proper N:P ratio’s for different fertilization rates with the fertilizers available to farmers in West-Shewa and Jimma (two major maize belts in Ethiopia). The trials were conducted with additional funding from the TAMASA project and in collaboration with EIAR. As the latter institute is involved in conducting fertilizer trials and the development of recommendations, this collaboration also aimed at forming an appropriate entry point for institutionalization of the decision support tool that is being developed.